A Pilot Study on Organizational Justice Scale for Student Organization: Result of Reliability and Validity - Thabrany Makmur Noerama; Catur Kurniawan; Tri Na’imah (Proceedings Series on Social Sciences & Humanities, 2021)
Organizational justice is an individual's fair perception of organizational decisions taken by its leaders. Researchers conducted a psychometric analysis to determine the validity and reliability of the organizational justice scale. The organizational justice scale is based on three dimensions: distributive justice, procedural justice, and interactional justice. The pilot study involved 36 students who were members of the Universitas Muhammadiyah Purwokerto, Indonesia. The validity test uses content validity, product-moment item selection while measuring reliability using Cronbach's alpha which is analyzed using SPSS version 25. The analysis results prove that 32 items are feasible and reliable with Cronbach's alpha value of 0.948. Thus, the organizational justice scale can be used for research on student organizations.